Apparent digestibility of nutrients, energy, and amino acid of nontoxic and detoxified physic nut cakes for Nile tilapia - Hisano, Hamilton; Lopes Della Flora, Marco Aurélio; Pilecco, José Luiz; Mendonça, Simone (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the apparent digestibility coefficients of nutrients, energy, and amino acids of nontoxic and detoxified physic nut cakes treated with solvent plus posterior extrusion, for Nile tilapia. The apparent digestibility coefficients of crude protein and gross energy were higher for detoxified than for nontoxic physic nut cake. However, the apparent digestibility coefficient of ether extract of the nontoxic physic nut cake was higher than that of the detoxified one. The apparent digestibility coefficient of amino acids of both feed ingredients was superior to 80%, except for glycine, for the nontoxic psychic nut cake, and for threonine, for the detoxified one. Nontoxic and detoxified physic nut cakes show apparent digestibility coefficient values equivalent to those of the other evaluated oilseeds and potential for inclusion in Nile tilapia diets.